Electrodeposited materials for electrocatalysis and electrochemical sensing - Li, Xinyu (Curtin University, 2022)
In this work, electrodeposition method has been proved to be better than hydrothermal method, and different electrodeposited materials are successfully synthesised and utilized for electroctalysis as well as sensing, the comparisons were conducted systematically by composation study, OER application study, as well as sensing behaviors towards gluose, methylparaben and dopamine.